On power quality control center for providing unbundled power quality services - Zhan, Yanqin (2008)
Using Power Quality Control Center (PQCC) to provide unbundled power quality services is investigated in this thesis. It begins with a detailed analysis of the PQCC by developing its mathematical model. Then using the PQCC to mitigate upstream voltage sag effects on sensitive loads is examined. Next, a more realistic scheme of the PQCC is proposed under both steady-state and upstream voltage-sag state. Finally, the PQCC voltage sag ride-through capability is further improved by introducing a Series Compensator (SC).